Minimizing static VAR compensator capacitor size by using SMC and ASRFC controllers in smart grid with connected EV charger. (May 2019) - Gholami Farkoush, Saeid; Wadood, Abdul; Khurshaid, Tahir; Kim, Chang-Hwan; Rhee, Sang-Bong
Highlights: This paper proposes two controlling methods for SVC in smart grid with connected EV charger. SMC, ASRFC with a HVC are separately applied in the grid. This paper presents usage of proposed methods for decreasing size of capacitor and value of apparent power loss. The proposed scheme is validated through computer simulations of a 22.9-kV grid. Abstract: Electric Vehicles (EVs) play a pivotal role in reducing the emissions of greenhouse gases in the world. Currently demand for EVs has abruptly increased for transportation and other applications. Using more EVs causes an increasing load on the power system. Random EV charging yields voltage distortion, which results in an unbalanced grid. In a distributed system, the connection of EVs to the grid may diminish the power factor, which increases the apparent power loss. The Static VAR Compensator (SVC), which is a FACTS device, is applied to the power system to compensate the voltage distortions and apparent power loss. In this paper, two controlling methods are contemplated and tested in a SVC to reduce the apparent power loss and minimize the capacitor size of the SVC in comparison with the conventional control method in a SVC. Proposed methods are also compared with the conventional control method used for SVC. The Slide Mode Controller (SMC) and Asymmetric Synchronous Reference Frame Controller (ASRFC) with a Harmonic Voltage Compensator (HVC) are separately applied in the grid. This paper presents usage of SMC and ASRFC methods for decreasing size of capacitor and value of apparent power loss through computer simulations of a 22.9-kV grid. With application of new controllers, apparent power loss of grid will be reduced as compared with conventional method of SVC controller. Moreover, the size of SVC capacitor can also be reduced.